2006
DOI: 10.1002/jat.1132
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic and aneugenic properties of an imidazole derivative

Abstract: To contribute to a more accurate characterization of the mutagenic and aneugenic effects of thiabendazole (TBZ), a widely used antiparasitic and food preservative drug, the induction of sister chromatid exchanges (SCEs) and mitotic spindle anomalies as cytogenetic end-points were investigated. Studies were carried out in Chinese hamster ovary (CHO) cells and human peripheral blood lymphocytes. A significant dose-dependent increase in SCE frequency was observed in CHO cells with S9-Mix (P < 0.01) in the 50-100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our present observations revealed that IVM and ivomec ® failed to accumulate mitotic cells and prolonged the average cell generation time in CHO K1 cells. Both IVM-and ivomec ® -treated CHO K1 cultures exhibited a significant decrease at 50.0-250.0 g/ml concentration-range in the mitotic index as well as in the PRI which are considered as two informative biomarkers as suggested elsewhere [34,35]. These authors pinpointed both markers as good and reliable endpoints related to cytotoxicity and cellular proliferation kinetics.…”
Section: Discussionmentioning
confidence: 88%
“…Our present observations revealed that IVM and ivomec ® failed to accumulate mitotic cells and prolonged the average cell generation time in CHO K1 cells. Both IVM-and ivomec ® -treated CHO K1 cultures exhibited a significant decrease at 50.0-250.0 g/ml concentration-range in the mitotic index as well as in the PRI which are considered as two informative biomarkers as suggested elsewhere [34,35]. These authors pinpointed both markers as good and reliable endpoints related to cytotoxicity and cellular proliferation kinetics.…”
Section: Discussionmentioning
confidence: 88%
“…As reported by Louzada et al (2010) and Carballo et al (2006), most tumours and tumour cell lines exhibit numerical and/or structural aberrations. It is well known that some members of the fungicide class (fluconazole, myclobutanil, triadimefon, propiconazole) have been established to be carcinogens in rodents (Sun et al, 2005(Sun et al, , 2006.…”
Section: Dosementioning
confidence: 63%
“…Such interaction between thiabendazole and tubulin monomers prevents the normal formation of MT arrays and the occurrence of mitotic processes mediated by MT, such as chromatid segregation and cytokinesis. Instead, the presence of multipolar spindles has been reported in animal cells exposed to thiabendazole, such as CHO cells [23,24]. Their formation by direct interference of thiabendazole with tubulin would be associated with the centrosomes.…”
Section: Discussionmentioning
confidence: 99%